Wound healing activity of Alternanthera brasiliana Kuntze and its anti oxidant profiles in experimentally induced diabetic rats - Chandana Choudhury Barua, Shameem Ara Begum, Debesh Chandra Pathak and Rumi Saikia Bora (Journal of Applied Pharmaceutical Science, 2013)
Alternanthera brasiliana Kuntze is a neotropical native species used against inflammation, cough and diarrhea etc. Traditionally it is used as hemostatic in north east India, but its excellent wound healing activity in excision, incision, aged, burn, immunocompromised wound were reported by us. Keeping in mind the delayed healing of wound in diabetic patients and its complications, the present study was undertaken to evaluate the healing efficacy of topical application of Alternanthera brasiliana in experimentally induced diabetic wounds in Sprague Dawley rats. The animals were divided into three groups of six animals each. Group I is control, group II is treated with topical application of the extract and group III is used as standard. Prohealing activity was assessed by wound contraction, histopathological study, modulation of enzymatic and non enzymatic parameters. There was significant (P
Keywords: Alternanthera brasiliana Kuntze. Antioxidants. Diabetes. Wound healing activity.